Spectrum of Electroencephalographic Findings in Seizures under 6 months aged infants at a Tertiary Care Hospital - Dr. Lubna Riaz; Dr.Waqas Shafique; Dr. Fouzia Ishaq; Dr. Neelam Faryad; Dr. Muhammad Ali Sheikh; Dr. Naveed Shahzad (Aziz Fatimah Medical and Dental College, 2021)
Objectives: To determine the spectrum of electroencephalographic findings in epilepsy of infants under 6 months of age Methodology It was a cross-sectional study conducted in the Pediatrics Department, at Shaikh Zayed Hospital, Lahore from May 2018 till April 2019. One hundred and forty-two infants aged one to six months of both genders which were newly diagnosed having first episode of seizures recruited by non-probability purposive sampling. Infants with no seizures, any central nervous system abnormalities like meningomyelocele, spina bifida, encephalocele, microcephaly and already taking antiepileptic drugs were excluded. Patient's demographic characteristics, seizure pattern and EEG record was obtained on Performa. Frequencies and percentages were calculated. Results: The mean age of infant patients was 3.18±1.90 months (1-6 months). Of the 142 infant patients, 97 (68%) were male and 45 (32%) females with positive family history in 42 (30%) patients. Epilepsy pattern revealed 101 (71.1%) presented with generalized seizures while 23 (16.2%) had focal seizures. Only 1 (0.7%) child suffered from epilepsy syndromes while seventeen (12%) had unclassified seizures. EEG reporting showed 41 (29%) had abnormal tracing. Of these, 23 (16%) patients had abnormal focal while 15 (11%) had abnormal generalized frequency and only 3 (2%) were with undetermined reporting. Normal EEG was seen in 101 (71%) patients. Conclusion: Almost one-third of patients with epilepsy had abnormal EEG findings so antiepileptic therapy selection must be tailored on individual basis, with special focus on patient's history and clinical presentation.